2011
DOI: 10.1530/joe-10-0422
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a native angiotensin from an anciently diverged serine protease inhibitor in lamprey

Abstract: Angiotensinogen belongs to family A serine protease inhibitors (SERPIN family) and we have cloned and characterized SERPIN genes in two lamprey species, which possess all the properties of angiotensinogen. The putative angiotensinogens in lampreys can be considered as an evolutionary link between SERPIN and other angiotensinogen according to the phylogenetic analyses. The inferred sea lamprey angiotensinogen gene was expressed abundantly in liver and to a lesser extent in other tissues. The predicted lamprey a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Considerable amounts of data have demonstrated that, in addition to the two main effector peptides of the brain RAS, ANG II and ANG III, ANG IV, and to a lesser extend ANG 1-7 are implicated in various physiological functions notably body fluid homeostasis and blood pressure regulation but also pituitary hormone release, thermoregulation, sexual, eating and locomotor behaviors, metabolism, learning, and memory (28,29,35,36,42,54). Compared with the central actions of the RAS on cardiovascular regulations, studies on the ventilatory effect are sparse and only the action of ANG II has been explored with conflicting results in mammals (13,31,33,37,41,50).The RAS has an ancient evolutionary history and most of its components are present in lampreys, elasmobranchs, and teleosts (29,32,38,46,53). In contrast to the well-known peripheral cardiovascular and osmoregulatory effects of ANG II (5,32,45), studies on the central action are sparse in fishes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable amounts of data have demonstrated that, in addition to the two main effector peptides of the brain RAS, ANG II and ANG III, ANG IV, and to a lesser extend ANG 1-7 are implicated in various physiological functions notably body fluid homeostasis and blood pressure regulation but also pituitary hormone release, thermoregulation, sexual, eating and locomotor behaviors, metabolism, learning, and memory (28,29,35,36,42,54). Compared with the central actions of the RAS on cardiovascular regulations, studies on the ventilatory effect are sparse and only the action of ANG II has been explored with conflicting results in mammals (13,31,33,37,41,50).The RAS has an ancient evolutionary history and most of its components are present in lampreys, elasmobranchs, and teleosts (29,32,38,46,53). In contrast to the well-known peripheral cardiovascular and osmoregulatory effects of ANG II (5,32,45), studies on the central action are sparse in fishes.…”
mentioning
confidence: 99%
“…The RAS has an ancient evolutionary history and most of its components are present in lampreys, elasmobranchs, and teleosts (29,32,38,46,53). In contrast to the well-known peripheral cardiovascular and osmoregulatory effects of ANG II (5,32,45), studies on the central action are sparse in fishes.…”
mentioning
confidence: 99%
“…Receptor internalization is triggered by ligand concentrations comparable to those in mammals and with similar kinetics [36]. Fourthly, injection of lamprey angiotensin II at 100–1000 pmol/kg provokes a cardiovascular response in cannulated conscious lampreys [37]. Blood pressure, however, is transiently decreased by the peptide, pointing to differences in pressure control mechanisms of lampreys and mammals.…”
Section: Discussionmentioning
confidence: 94%
“…47 Serine proteases promote cartilage destruction in osteoarthritis. 48,49 Here, greater expression of CSF angiotensinogen in CSM-affected dogs, which had marked osteoarthritic changes of their cervical vertebrae, might be a compensatory increase in an attempt to inhibit the excess of protease activity that occurs in osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%